Effects of haptic feedback in dual-task teleoperation of a mobile robot - Corujeira, J. (2018)
Teleoperation system usage is challenging to human operators, as this system has a predominantly visual interface that limits the ability to acquire situation awareness, (e.g. maintain a safe teleoperation). This limitation coupled with the dual-task problem of teleoperating a mobile robot, negatively affects the operators cognitive load and motor skills. Our motivation is to offload some of the visual information to a secondary perceptual channel (haptic), by proposing an assisted teleoperation system. This system uses haptic feedback to alert the operator of obstacle proximity, without directly influencing the operator’s command inputs. The objective of this paper, is to evaluate and validate the efficacy of our system’s haptic feedback, by providing the obstacle proximity information to the operator. The user experiment was conducted to emulate the dual-task problem, by having a concurrent task for cognitive distraction. Our results showed significant differences in time to complete the navigation task and the duration of collisions, between the haptic feedback condition and the control condition.